Methodology of Developing Technical Actions of Young Goalkeepers during Handball Training - Majitovich, Umarov Komil; Azzamqulovich, Tursunqulov Elmurod; Ilhomovich, Mirzaev Ibrohim (International Journal on Integrated Education, 2023)
This study looks at the characteristics that help juvenile goalkeepers improve their accuracy when receiving, returning, and passing the ball during handball practice. Young goalkeepers' ability to receive, return, and move the ball with greater efficiency has been improved through the development of a series of training microcycles and exercises. It has been established that, during the initial phase of training, special attention needs to be paid to the proper construction of the goalkeepers' precise motions for receiving, returning, and transferring the ball.